2009
DOI: 10.1093/aob/mcp026
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts in floral nectar: a quantitative survey

Abstract: Incorporating nectar yeasts into the scenario of plant-pollinator interactions opens up a number of intriguing avenues for research. In addition, with yeasts being as ubiquitous and abundant in floral nectars as revealed by this study, and given their astounding metabolic versatility, studies focusing on nectar chemical features should carefully control for the presence of yeasts in nectar samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
247
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(265 citation statements)
references
References 47 publications
15
247
0
3
Order By: Relevance
“…Bombus vosnesenskii and Xylocopa micans) may also visit M. aurantiacus flowers. Flowers can persist for approximately 6 -10 days [22] and contain up to 10 ml of nectar [21], in which both yeasts [23] and bacteria frequently attain densities of 10 4 CFUs (colony forming units) per ml, similar to densities reported in other systems [24]. At JRBP, bacterial densities ranged from 0 to 10 4 CFUs per ml, with an average of 350 CFUs per ml among flowers exposed to pollinators (n ¼ 82 flowers).…”
Section: Methods (A) Study Organismssupporting
confidence: 62%
See 2 more Smart Citations
“…Bombus vosnesenskii and Xylocopa micans) may also visit M. aurantiacus flowers. Flowers can persist for approximately 6 -10 days [22] and contain up to 10 ml of nectar [21], in which both yeasts [23] and bacteria frequently attain densities of 10 4 CFUs (colony forming units) per ml, similar to densities reported in other systems [24]. At JRBP, bacterial densities ranged from 0 to 10 4 CFUs per ml, with an average of 350 CFUs per ml among flowers exposed to pollinators (n ¼ 82 flowers).…”
Section: Methods (A) Study Organismssupporting
confidence: 62%
“…Indeed, preliminary results of our ongoing research indicate that the honeybee, Apis mellifera, also prefers yeast-colonized nectar to bacteria-colonized nectar. Moreover, although our study involved only one species each of yeasts and bacteria, M. reukaufii is the dominant yeast species at our field site [23] and commonly found in the nectar of many other plants [24]. Further, Gluconobacter is a member of the acetic acid bacteria, many of which frequently occur in nectar (e.g.…”
Section: (B) Generality Of Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Natural variation in ecologically consequential nectar traits (e.g., sugar and amino acid concentration) not only reflects intrinsic features of plant species and individuals, but also depends on the action of a variety of extrinsic abiotic and biotic factors unrelated to the plants themselves (Corbet 1978, Nicolson et al 2007, Baude et al 2011. One infrequently acknowledged biotic factor potentially altering nectar features is nectardwelling yeasts, which recent studies have shown to abundantly populate animal-pollinated flowers worldwide (Brysch-Herzberg 2004, Herrera et al 2009). Among other effects, nectar yeasts can alter the composition and concentration of sugars and amino acids in nectar, contribute to the emission of floral volatiles, and warm the nectar in relation to the surrounding air (Raguso 2004, Wiens et al 2008, Canto and Herrera 2012.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low fructose concentration in uncovered area can be related with low density of honeybees recorded or low presence of another preferential pollinator of fructose. For some researchers, the pollinators can affect the nectar composition (Canto et al, 2008;Herrera et al, 2009). In Helleborus foetidus, for example, some species of Bombus unchain modifications in sugar composition in nectar reducing the sucrose percentage, and rising the fructose and glucose percentage (Canto et al, 2008).…”
Section: Sugar Concentration In Nectarmentioning
confidence: 99%